Subchronic toxicity of oral deltamethrin in laying chickens - Liu, Yiming; Han, Mingyue; Liu, Chunshuang; Tang, Yaoxin; Jia, Ming; Chen, Xiaojie; Liang, Haijun; Gao, Yunfeng; Gu, Xu (Frontiers in Veterinary Science, 2022)
The aim of the present study was to examine deltamethrin subchronic toxicity in laying chickens. One hundred and twelve laying chickens were randomly assigned to 13 experimental groups treated with deltamethrin (n = 8) and one control group not treated with deltamethrin (n = 8). Tissue samples were collected during and after treatment for weighing and histopathological analysis. A single dose of deltamethrin (20 mg·kg-1·BW·d) was administered orally to laying chickens each day for 14 d. Deltamethrin was found to have no significant effect on relative tissue or organ weight in laying chickens (p > 0.05). The activities of aspartate aminotransferase and cholinesterase in the plasma gradually decreased over time in the deltamethrin treatment group (p < 0.05). Plasma concentrations of urea nitrogen, uric acid, cholesterol, triglycerides, and creatinine significantly increased during treatment (p < 0.05). Deltamethrin residue caused significant liver damage and loss of intestinal villous epithelium. The intestinal wall thickness, villus height, and crypt depth of laying chickens were altered by deltamethrin treatment. After treatment was withdrawn, intestinal repair was more extensive than liver repair.